EFEKTIVITAS BELT AND ROAD INITIATIVE (BRI) SEBAGAI STRATEGI GEOPOLITIK TIONGKOK PASCA KEMUNCULAN GLOBAL GATEWAY (2021-2024) - Yulisa, Dhea; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
More than a decade after its launch, under Xi Jinping’s leadership has successfully dominated the global economic landscape and expanded China’s geopolitical influence. In response, the European Union introduced the Global Gateway as an alternative infrastructure funding initiative, promoting sustainability and mitigating the risks of ‘debt trap’ associated with China’s BRI. This study analyzes the effectiveness of the Belt and Road Initiative (BRI) as a geopolitical strategy for China following the emergence of the Global Gateway. Employing a qualitative methodology, data collection was conducted through document analysis from books, journals, articles, and websites. The study adopts a Realist perspective and utilizes Joseph Nye's Soft Power Theory. The research should explain how Global Gateway marks a new chapter in global economic competition. Evidence suggests that China's BRI remains more promising compared to the EU's initiative, as indicated by political stability and an increasing number of partnerships. This is attributed to BRI's lending system, which appears less encumbered by internal complexities faced by the European Union. Keywords: Belt and Road Initiative, Global Gateway, Geopolitics.